The transmembrane protein LRIG1 triggers melanocytic tumor development following chemically induced skin carcinogenesis. Issue 8 (31st March 2021) - Hoesl, Christine; Fröhlich, Thomas; Posch, Christian; Kneitz, Hermann; Goebeler, Matthias; Schneider, Marlon R.; Dahlhoff, Maik
Abstract : The incidence of melanoma and nonmelanoma skin cancer has increased tremendously in recent years. Although novel treatment options have significantly improved patient outcomes, the prognosis for most patients with an advanced disease remains dismal. It is, thus, imperative to understand the molecular mechanisms involved in skin carcinogenesis in order to develop new targeted treatment strategies. Receptor tyrosine kinases (RTK) like the ERBB receptor family, including EGFR/ERBB1, ERBB2/NEU, ERBB3, and ERBB4, are important regulators of skin homeostasis and their dysregulation often results in cancer, which makes them attractive therapeutic targets. Members of the leucine‐rich repeats and immunoglobulin‐like domains protein family (LRIG1‐3) are ERBB regulators and thus potential therapeutic targets to manipulate ERBB receptors. Here, we analyzed the function of LRIG1 during chemically induced skin carcinogenesis in transgenic mice expressing LRIG1 in the skin under the control of the keratin 5 promoter (LRIG1‐TG mice). We observed a significant induction of melanocytic tumor formation in LRIG1‐TG mice and no difference in papilloma incidence between LRIG1‐TG and control mice. Our findings also revealed that LRIG1 affects ERBB signaling via decreased phosphorylation of EGFR and increased activation of the oncoprotein ERBB2 during skin carcinogenesis. The epidermal proliferation rate was significantly decreased during epidermal tumorigenesis under LRIG1 overexpression, and the apoptosis marker cleaved caspase 3 was significantly activated in the epidermis of transgenic LRIG1 mice. Additionally, we detected LRIG1 expression in human cutaneous squamous cell carcinoma and melanoma samples. Therefore, we depleted LRIG1 in human melanoma cells (A375) by CRISPR/Cas9 technology and found that this caused EGFR and ERBB3 downregulation in A375 LRIG1 knockout cells 6 h following stimulation with EGF. In conclusion, our study demonstrated that LRIG1‐TG mice develop melanocytic skin tumors during chemical skin carcinogenesis and a deletion of LRIG1 in human melanoma cells reduces EGFR and ERBB3 expression after EGF stimulation. Abstract : The tyrosine kinase inhibitor leucine‐rich repeats and immunoglobulin‐like domains 1 (LRIG1) were overexpressed in the mouse skin to assess its function in this organ. While LRIG1 efficiently inactivated EGFR, epidermal LRIG1 excess showed no impact in experimentally induced skin carcinogenesis. However, transgenic animals developed remarkable melanocytic nevi induced by cleaved LRIG1, indicating a potential role for LRIG1 in melanoma.